2020
DOI: 10.3390/cli8100112
|View full text |Cite
|
Sign up to set email alerts
|

Convection Parametrization and Multi-Nesting Dependence of a Heavy Rainfall Event over Namibia with Weather Research and Forecasting (WRF) Model

Abstract: Namibia is considered to be one of the countries that are most vulnerable to climate change due to its generally dry climate and the percentage of its population that rely on subsistence agriculture for their livelihoods. Early-warning systems are an important aspect of adapting to climate change. Weather forecasting relies on the use of numerical weather prediction models and these need to be configured properly. In this study, we investigate the effects of using multi-nests and a convection scheme on the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Given that the three events were selected because at least one ground observation reported over 90 mm of rainfall, we conclude that IMERG provides the best estimate of extreme rainfall. The QPE from TAMSAT for the 17 December 2016 and 21 January 2017 case studies is consistent with other recent studies in the region, in the sense that values were severely underestimated in simulating heavy rainfall associated with an ex-tropical cyclone [64] and a cut-off low system [66]. It may be noted that the ZMD station rainfall was used to calibrate the TAMSAT QPE [10,55].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Given that the three events were selected because at least one ground observation reported over 90 mm of rainfall, we conclude that IMERG provides the best estimate of extreme rainfall. The QPE from TAMSAT for the 17 December 2016 and 21 January 2017 case studies is consistent with other recent studies in the region, in the sense that values were severely underestimated in simulating heavy rainfall associated with an ex-tropical cyclone [64] and a cut-off low system [66]. It may be noted that the ZMD station rainfall was used to calibrate the TAMSAT QPE [10,55].…”
Section: Discussionsupporting
confidence: 87%
“…All of the model configurations underestimated rainfall in the outer domain for all three case studies. Somses et al [66], who used the same convection scheme as in the current study, and Champion and Hodges [71] found similar results, that switching on the convection scheme results in lower rainfall intensities. Steeneveld and Peerlings [75] compared simulations of a hail storm over the Netherlands using different convection schemes, and concluded that scale-aware convection schemes can be beneficial for the representation of deep convection in the gray zone.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The timing of the peak is found to be informed by the global model providing lateral boundary conditions, indicating a need to use global models with good skill when running dynamical downscalers. Previous other studies have shown that switching off the convection schemes results in higher rainfall intensity (e.g., [33,34]).…”
Section: Discussionmentioning
confidence: 90%
“…Some of the newer parameterization schemes were developed in a way that allows their behaviour to adapt with changing resolution, and these are called scale aware schemes, e.g., [31,32]. Somses et al [33] and Champion and Hodges [34] showed that switching off the convection scheme when a grid length of less than 5 km is used results in higher rainfall intensity being simulated. Furthermore, Steeneveld and Peerlings [29] indicated that the use of scale-aware schemes is beneficial for the representation of deep convection in the grey zones.…”
Section: Introductionmentioning
confidence: 99%